2020
DOI: 10.1002/ange.201914559
|View full text |Cite
|
Sign up to set email alerts
|

Structural Insight into IAPP‐Derived Amyloid Inhibitors and Their Mechanism of Action

Abstract: Designed peptides derived from the islet amyloid polypeptide (IAPP) cross‐amyloid interaction surface with Aβ (termed interaction surface mimics or ISMs) have been shown to be highly potent inhibitors of Aβ amyloid self‐assembly. However, the molecular mechanism of their function is not well understood. Using solution‐state and solid‐state NMR spectroscopy in combination with ensemble‐averaged dynamics simulations and other biophysical methods including TEM, fluorescence spectroscopy and microscopy, and DLS, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 52 publications
0
9
0
1
Order By: Relevance
“…311 Most oligomeric states had larger α-helical than β-sheet content, and in about 5% of the simulations β-barrel conformations were formed by pentamers and hexamers. Furthermore, the same research group reported that five fragments of amyloidogenic peptides, namely the cytotoxic hIAPP (19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29) and its Ser20Gly mutant as well as hIAPP (22)(23)(24)(25)(26)(27)(28), Aβ (16)(17)(18)(19)(20)(21)(22) and α-nuclein (68)(69)(70)(71)(72)(73)(74)(75)(76)(77)(78), formed oligomers with β-barrel content in DMD simulations while two non-toxic fragments (hIAPP (15)(16)(17)(18)(19)(20)(21)(22)(23)…”
Section: Dimerizationmentioning
confidence: 99%
See 3 more Smart Citations
“…311 Most oligomeric states had larger α-helical than β-sheet content, and in about 5% of the simulations β-barrel conformations were formed by pentamers and hexamers. Furthermore, the same research group reported that five fragments of amyloidogenic peptides, namely the cytotoxic hIAPP (19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29) and its Ser20Gly mutant as well as hIAPP (22)(23)(24)(25)(26)(27)(28), Aβ (16)(17)(18)(19)(20)(21)(22) and α-nuclein (68)(69)(70)(71)(72)(73)(74)(75)(76)(77)(78), formed oligomers with β-barrel content in DMD simulations while two non-toxic fragments (hIAPP (15)(16)(17)(18)(19)(20)(21)(22)(23)…”
Section: Dimerizationmentioning
confidence: 99%
“…333 Niu et al investigated the inhibition of Aβ aggregation by derivatives of IAPP whose design was inspired by the IAPP/Aβ cross-amyloid interaction surface. 334 The authors employed a combined experimental and computational approach based on fluorescence spectroscopy, solutionstate and solid-state NMR spectroscopy, transmission electron microscopy (TEM), dynamic light scattering, and MD simulations. The multi-disciplinary study revealed that a peptide derived from the two segments of IAPP (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18) and IAPP (22)(23)(24)(25)(26)(27)(28) (linked by an -RRR-tripeptide and with methylated backbone nitrogen on the Phe23 and Ala25) is disordered, has transient β-sheet content, and can oligomerize into colloid-like assemblies that can interact with Aβ40.…”
Section: Peptidesmentioning
confidence: 99%
See 2 more Smart Citations
“…Proton detection has become a popular tool [17][18][19][20] for investigating large biomolecules in recent years, and new strategies ranging from hardware development to isotope labelling have been developed. A wide variety of supramolecular assemblies [21,22] such as amyloid fibrils [23][24][25][26][27][28][29], membrane proteins, ribosomal subunits [30] and viral capsids [31][32][33] have meanwhile been studied with atomic resolution employing proton-detected MAS solid state NMR.…”
Section: Introductionmentioning
confidence: 99%